KONJUNGSI ANTARKLAUSA BAHASA MELAYU JAMBI DI DESA SUNGAI GELAM KECAMATAN SUNGAI GELAM KABUPATEN MUARO JAMBI - Susanti ,; Rustam Rustam; Wawan Gunawan (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2016)
ABSTRACT The purpose of this study is to describe the use of conjunctions in complex sentences antarklausa equivalent and multilevel, and the semantic relationship between Jambi Malay language. Descriptive and qualitative research methods. The conclusion of this research is the combination used by Jambi Malay community in Sungai Gelam and, seo, but apo, when, suda tu, since, time, selamo, temporary, sambǝl, sebelom, habi, until, kalu, origin, kalu misalnyo, kalu-kalu, reproduce, supayo, biakpun, baik, keno, makonyo, pakek, kalu, nang, samo ... with, lebeh ... daripado. Suggestion of research to the reader in order to conduct further research more deeply because this research is still limited to the use of conjunction in complex sentence between equivalent and terraced village Gelam Gelam Sungai Gelam Muaro Jambi.prespenation of speech, so that will be obtained by information or data deeper. Keywords: coordinating conjunctions, subordinating conjunctions